‘Promising’? ‘Hiring’? ‘Coloring’? ‘Pawning’? Reflections on the notion of artistic ‘commitment’ in the Indo-European arena - Henry DANIELS (E-REA)
This article looks first at the contemporary and historical, formal and semantic background of the English verb commit and its various uses in the domain of artistic production. The second part of the article looks at the representations of the notion of ‘commitment’ in present-day French, German and Italian. The study brings to light fundamental intra- and inter-language differences with regard to the representation of the notion, leading to the conclusion that there is, as far as artistic commitment is concerned, no common semantic backdrop inherited from Antiquity or Indo-European.